The Association Between Salt and Potassium Intake with Multiple Sclerosis - Sarah Ghorbani; Hamidreza Hatamian; Amirhossain Mahmoudzadeh; Sina Raeisi; Mohammadjavad Eslami; Masoud Etemadifar; Fatemeh Shafaei (Caspian Journal of Neurological Sciences, 2019)
Background: The number of patients with Multiple Sclerosis (MS) is increasing in Iran. Studies have shown that high sodium chloride (salt) and low potassium intake are associated with the development of MS. High physiological salt concentrations can lead to the induction of Interleukin-17 (IL-17) accompanied by the excessive generation of helper T-17 cells (Th-17). This cytokine plays a critical role in the pathogenesis of autoimmune diseases. This is while potassium supplementation has a blocking effect on IL-17 production. Objectives: Because of the role of salt and potassium in Th 17 development, we hypothesized that sodium chloride (NaCl) would be higher and potassium (K) would be lower in MS patients than healthy controls. Therefore, we investigated the association between salt and potassium intake with MS in Isfahan City population, Iran. Materials & Methods: A case-control study containing 23 patients and 23 healthy controls was performed in Isfahan City, Iran, 2016. NaCl and K levels were measured in 24-h urine. Using the Chi-square test, the patients’ laboratory values were compared with the healthy controls. The level of significance was set at P<0.05 in all analyses. All calculations were performed in SPSS, version 23.0. Results: In this study, urine Na levels were somewhat higher in cases than in controls (Interquartile Range [IQR]; 160[140-211] mEq/24 h vs. 128[83-166] mEq/24 h]) (P=0.027). These results show a significant relationship between urine-Na and MS. Urine k concentrations were lower in cases than controls [IQR; 47(27-70) mEq/24 h vs. 50(29-56) mEq/24 h] but we did not find a significant difference between two groups (P=0.807). Conclusion: Based on this study, a high level of sodium intake may be associated with MS; however, we did not find a significant difference between patients and controls with regard to potassium level.